Optimalisasi Produksi Alat Gali Muat Komatsu PC 400-18 dengan Metode Overall Equipment Effectiveness (OEE) pada Pengupasan Lapisan Overburden di PT. Surya Global Makmur Jobsite Pemusiran, Kabupaten Sarolangon, Provinsi Jambi - Fitri Nadia; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Based on production data of stripping overburden from January to October 2019 in PT.Surya Global Makmur, the production of stripping overburden didn’t reach the target. This iscaused by standby times and breakdown times which causes the operating time and productivityto be low. To determine the potential improvement of a production process and the effectivenessof use an equipment, it is necessary to do an analysis using overall eqipment effectiveness (OEE)method. From the OEE value that hasn’t reached the ideal limit, six big losses analysis is carriedout to determine which losses that give the biggest contribution in the decreasing of equipmentproductivity. Then fishbone method is used to find the cause and effect of the decreasing ofequipment productivity and evaluation by referring to the result of identification of six big losses.After analysis and improvement methods are carried out, the production of Komatsu PC 400-18exceeded the target that has been planned. But the value of OEE is still < 85% haven’t achievedthe world-class OEE >85%, it can be concluded that the state of equipment is not good. It is betterto do improvement to reduced speed losses.Keywords: Produksi, Komatsu PC 400, Overall Equipment Effectiveness, Six Big Losses, Metode Fishbone